4.1N-Mediated Interactions and Functions in Nerve System and Cancer - Yang, Qin; Liu, Jing; Wang, Zi (Frontiers in Molecular Biosciences, 2021)
Scaffolding protein 4.1N is a neuron-enriched 4.1 homologue. 4.1N contains three conserved domains, including the N-terminal 4.1-ezrin-radixin-moesin (FERM) domain, internal spectrin-actin-binding (SAB) domain and C-terminal domain (CTD). The interspersed between the three domains are nonconserved domains, including U1, U2 and U3. The role of 4.1N was first reported in the nerve system. Then, extensive studies reported the role of 4.1N in cancers and other diseases. 4.1N performs numerous vital functions in signaling transduction by interacting, locating, supporting and coordinating different partners and is involved in the molecular pathogenesis of various diseases. In this review, recent studies on the interactions between 4.1N and its contactors (including the α7AChr, IP3R1, GluR1/4, GluK1/2/3, mGluR8, KCC2, D2/3Rs, CASK, NuMA, PIKE, IP6K2, CAM 1/3, βII spectrin, flotillin-1, pp1 and 14-3-3) , and the 4.1N-related biological functions in the nerve system and cancers are specifically and comprehensively discussed. This review provides critical detailed mechanistic insights into the role of 4.1N in disease relationships.